KBP-066A, a long-acting dual amylin and calcitonin receptor agonist, induces weight loss and improves glycemic control in obese and diabetic rats - K.V. Andreassen; A.T. Larsen; N. Sonne; K.E. Mohamed; M.A. Karsdal; K. Henriksen (Elsevier, 2021)
Objective: Dual amylin and calcitonin receptor agonists (DACRAs) are novel therapeutic agents that not only improve insulin sensitivity but also work as an adjunct to established T2DM therapies. DACRAs are currently administered once daily, though it is unknown whether DACRAs with increased plasma half-life can be developed as a once-weekly therapy. Methods: The in vitro potencies of the KBP-066A and KBP-066 (non-acylated) were assessed using reporter assays. Acylation functionality was investigated by a combination of pharmacokinetics and acute food intake in rats. in vivo efficacies were investigated head-to-head in obese (HFD) and T2D (ZDF) models. Results: In in vitro, KBP-066A activated the CTR and AMY-R potently, with no off-target activity. Acylation functionality was confirmed by acute tests, as KBP-066A demonstrated a prolonged PK and PD response compared to KBP-066. Both compounds induced potent and dose-dependent weight loss in the HFD rat model. In ZDF rats, fasting blood glucose/fasting insulin levels (tAUC) were reduced by 39%/50% and 36%/47% for KBP-066 and KBP-066A, respectively. This effect resulted in a 31% and 46% vehicle-corrected reduction in HbA1c at the end of the study for KBP-066 and KBP-066A, respectively. Conclusions: Here, we present pre-clinical data on an acylated DACRA, KBP-066A. The in vivo efficacy of KBP-066A is significantly improved compared to its non-acylated variant regarding weight loss and glycemic control in obese (HFD) and obese diabetic rats (ZDF). This compendium of pre-clinical studies highlights KBP-066A as a promising, once-weekly therapeutic agent for treating T2DM and obesity.